2016
DOI: 10.1038/icb.2016.63
|View full text |Cite
|
Sign up to set email alerts
|

Stat3 and C/EBPβ synergize to induce miR‐21 and miR‐181b expression during sepsis

Abstract: Myeloid-derived suppressor cells (MDSCs) increase late sepsis immunosuppression and mortality in mice. We reported that microRNA (miR) 21 and miR-181b expression in Gr1+CD11b+ myeloid progenitors increase septic MDSCs in mice by arresting macrophage and dendritic cell differentiation. Here, we report how sepsis regulates miR-21 and miR-181b transcription. In vivo and in vitro binding studies have shown that C/EBPα transcription factor, which promotes normal myeloid cell differentiation, binds both miRNA promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 59 publications
3
68
0
Order By: Relevance
“…We also reported that C/EBPα, and not C/EBPβ, binds the same consensus motif at miR-21 and miR-181b promoters and is required for generating immune competent Gr1 + CD11b + cells (McClure et al , 2017), thus disrupting expression of miR-21 and miR-181b. In this study and using Chromatin immunoprecipitation (ChIP) assay, we show that C/EBPβ binding at the miR-21 promoter in sepsis but not sham Gr1 + CD11b + cells from the control mice, which further increased in late sepsis cells (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…We also reported that C/EBPα, and not C/EBPβ, binds the same consensus motif at miR-21 and miR-181b promoters and is required for generating immune competent Gr1 + CD11b + cells (McClure et al , 2017), thus disrupting expression of miR-21 and miR-181b. In this study and using Chromatin immunoprecipitation (ChIP) assay, we show that C/EBPβ binding at the miR-21 promoter in sepsis but not sham Gr1 + CD11b + cells from the control mice, which further increased in late sepsis cells (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Morever, mice with C/EBPβ conditional knockout survive late sepsis and generate Gr1 + CD11b + immune competent myeloid progenitors (McPeak et al , 2017). C/EBPβ induces miR-21 and miR-181b to generate immunosuppressive Gr1 + CD11b + in the bone marrow of septic mice (McClure et al , 2017). In this study, we hypothesized that genetic deletion Cebpb will disrupt the path that leads to Gr1 + CD11b + MDSC generation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations